Problems with Bone Health and the Influencing Factors of Bone Mineral Density in Women across the Life Cycle - Nami Chun; Hyunju Chae (Korean Society of Women Health Nursing, 2015)
PURPOSE: This study was conducted to identify the problem of bone health and potential influencing factors of bone mineral density (BMD) for women across the life cycle of menopause. METHODS: Complex sampling design data analysis was performed on the fifth Korea National Health and Nutrition Examination Survey 2010 in order to identify the problems with bone health, BMD and its influencing factors in 3,499 women who answered the menopausal status. Women's life cycle was categorized by premenopausal, postmenopausal, and elderly. RESULTS: 35.1% of premenopausal women, 73.3% of postmenopausal women, and 96.0% of elderly women had problems with bone health that were related to low BMD. Influencing factors of BMD were residential area, alcohol drinking, and body mass index (BMI) for premenopausal women; age, residential area, education, marital status, income, and BMI for postmenopausal women; and age, education, and BMI for elderly women. CONCLUSION: Problems with bone health required to be considered as a major health problem in all women regardless their life cycle. Interventions to maximize BMD need to be developed by considering its influencingfactors across the women's life cycle.